Foreign exchange option and returns based correlation forecasts: evaluation and two applications - Olli Castrén; Stefano Mazzotta (European Central Bank (ECB), 2005)
We compare option-implied correlation forecasts from a dataset consisting of over 10 years of daily data on over-the-counter (OTC) currency option prices to a set of return-based correlation measures and assess the relative quality of the correlation forecasts. We find that while the predictive power of implied correlation is not always superior to that of returns based correlations measures, it tends to provide the most consistent results across currencies. Predictions that use both implied and returns-based correlations generate the highest adjusted R2s, explaining up to 42 per cent of the realised correlations. We then apply the correlation forecasts to two policyrelevant topics, to produce scenario analyses for the euro effective exchange rate index, and to analyse the impact on cross-currency co-movement of interventions on the JPY/USD exchange rate.
Keywords: F31; F37; G15; 330; Correlation forecasts; currency options data; effective exchange rate; Währungsderivat; Optionspreistheorie; Euro; US-Dollar; Yen; Korrelation